Efektivitas Pendidikan Kesehatan dalam Meningkatkan Pengetahuan Pencegahan Skabies pada Penderita Skabies - Yutanti, Wulan Tri; Setiyono, Andik (Universitas Pahlawan Tuanku Tambusai, 2025)
Scabies is one of the most neglected tropical diseases. Scabies is contagious and spreads quickly due to the use of shared personal items, improper prevention and control, and unhealthy environmental conditions. This condition can be prevented if the community knows the characteristics and how to prevent and control scabies. Based on these conditions, the purpose of implementing this activity is to increase the knowledge of people with scabies about how to prevent scabies. The lecture method was used to deliver health education materials on the prevention of scabies. Respondents' knowledge was evaluated by comparing the mean scores of pre-test and post-test. Based on the Wilcoxon test results, there was a significant difference between the mean pre-test and post-test knowledge scores (p-value 0.05). In the short term, health education results in a change or increase in knowledge, but if given continuously and sustainably, it will affect behavior as a medium-term impact.